A Medicago truncatula phosphate transporter indispensable for the arbuscular mycorrhizal symbiosis - Javot, Hélène (National Academy of Sciences, 2007)
The arbuscular mycorrhizal (AM) symbiosis is a mutualistic endosymbiosis formed by plant roots and AM fungi. Most vascular flowering plants have the ability to form these associations, which have a significant impact on plant health and consequently on ecosystem function. Nutrient exchange is a central feature of the AM symbiosis, and AM fungi obtain carbon from their plant host while assisting the plant with the acquisition of phosphorus (as phosphate) from the soil. In the AM symbiosis, the fungus delivers P(i) to the root through specialized hyphae called arbuscules. The molecular mechanisms of P(i) and carbon transfer in the symbiosis are largely unknown, as are the mechanisms by which the plant regulates the symbiosis in response to its nutrient status. Plants possess many classes of P(i) transport proteins, including a unique clade (Pht1, subfamily I), members of which are expressed only in the AM symbiosis. Here, we show that MtPT4, a Medicago truncatula member of subfamily I, is essential for the acquisition of P(i) delivered by the AM fungus. However, more significantly, MtPT4 function is critical for AM symbiosis. Loss of MtPT4 function leads to premature death of the arbuscules; the fungus is unable to proliferate within the root, and symbiosis is terminated. Thus, P(i) transport is not only a benefit for the plant but is also a requirement for the AM symbiosis.